Research as care: practice-based knowledge translation as transformative learning through video-reflexive ethnography. Issue 1 (2nd January 2023) - Hor, Su-yin; Dadich, Ann; Gionfriddo, Michael R.; Noble, Christy; Wyer, Mary; Mesman, Jessica
ABSTRACT: Collaborative approaches to knowledge translation seek to make research useful and applicable, by centring the perspectives and concerns of healthcare actors (rather than researchers) in problem formulation and solving. Such research thus involves multiple actors, in interaction with pre-existing ecologies of knowledge and expertise. Although collaboration is emphasised, conflict, dissonance, and other tensions, may arise from the multiplicity of perspectives and power dynamics involved. Our article examines knowledge translation in this space, as both empirical focus and research methodology. Drawing from practice theory and critical pedagogy, we describe knowledge translation as a situated and social process of transformative learning, enabled by reflexive dialogue about practice, and supported by care. With examples from five studies across two countries, we show that practice-based knowledge translation can be mediated by researchers, using video-reflexive ethnography. We describe the importance (and features) of practices of care in these studies, that created psychological safety for transformative learning. We argue that attempts to transform and improve healthcare must account for sustained and reciprocal care, both for, and between, those made vulnerable in the process, and that knowledge translation can, and should, be a process of capacity strengthening, with care as a core principle and practice.